Decreased Enterobacteriaceae translocation due to gut microbiota remodeling mediates the alleviation of premature aging by a high‐fat diet. Issue 2 (25th December 2022) - Xu, Kang; Guo, Yannan; Wang, Yida; Ren, Yu; Low, Vivien; Cho, Sungyun; Ping, Lu; Peng, Kezheng; Li, Xue; Qiu, Ying; Liu, Qingfei; Li, Zhongchi; et al.
Abstract: Aging‐associated microbial dysbiosis exacerbates various disorders and dysfunctions, and is a major contributor to morbidity and mortality in the elderly, but the underlying cause of this aging‐related syndrome is confusing. SIRT6 knockout (SIRT6 KO) mice undergo premature aging and succumb to death by 4 weeks, and are therefore useful as a premature aging research model. Here, fecal microbiota transplantation from SIRT6 KO mice into wild‐type (WT) mice phenocopies the gut dysbiosis and premature aging observed in SIRT6 KO mice. Conversely, an expanded lifespan was observed in SIRT6 KO mice when transplanted with microbiota from WT mice. Antibiotic cocktail treatment attenuated inflammation and cell senescence in KO mice, directly suggesting that gut dysbiosis contributes to the premature aging of SIRT6 KO mice. Increased Enterobacteriaceae translocation, driven by the overgrowth of Escherichia coli, is the likely mechanism for the premature aging effects of microbiome dysregulation, which could be reversed by a high‐fat diet. Our results provide a mechanism for the causal link between gut dysbiosis and aging, and support a beneficial effect of a high‐fat diet for correcting gut dysbiosis and alleviating premature aging. This study provides a rationale for the integration of microbiome‐based high‐fat diets into therapeutic interventions against aging‐associated diseases. Abstract : SIRT6 KO mice are characterized by a gut dysbiosis, particularly due to overabundant Escherichia coli colonization in gut and Enterobacteriaceae translocation into visceral organs, partly resulting in a shortened lifespan and premature aging. Crucially, a high‐fat diet improves gut dysbiosis, which positively correlates with extended lifespan and rescues premature aging in SIRT6 KO mice.